Normal embryonic stages of the Longnose Gar, Lepisosteus osseus - Long, Wilbur L (BioMed Central, 2001)
BACKGROUND: Gaps exist in the modern literature that describes patterns of development in living groups of actinopterygian fishes. Relatively recent descriptions of development exist for the teleost fishes, bowfin, sturgeon, paddlefish and bichirs. Such literature dealing with the gars is to be found in older work, done approximately a century ago. The present study concerns the gars, of which the garpike, Lepisosteus osseus, is a representative example. RESULTS: The embryonic period of life of this fish is divided, as required for experimentation, into 34 stages, from fertilization to exhaustion of the yolk supply. Diagnostic structural characteristics are cited for each stage, and the rate of development is indicated. CONCLUSIONS: Three features of development are especially noted that compare or contrast with other members of the Neopterygii, and with the Chondrostei. These are meroblastic cleavage, a well-defined yolk syncytial layer (ysl), and a pit at the posterodorsal edge of the blastoderm, which defines an overhanging dorsal lip. Meroblastic cleavage and the ysl in the garpike show an affinity to those character states in the teleosts, though not with Amia, the other neopterygian fish. The posterodorsal pit and dorsal lip are reminiscent of similar features in the Chondrostei. Lepisosteus is unique among the Neopterygii with respect to this character state. Such comparisons set the stage for a broader understanding of the mechanisms for development in these organisms, and of the evolutionary relationships between them.